2015
DOI: 10.1021/acs.jmedchem.5b00669
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol-Derived Compounds: A Basis for the Creation of New Pharmacological Agents for Cancer Prevention and Therapy

Abstract: Hydroxytyrosol [2-(3,4-dihydroxyphenyl)ethanol, HTyr] is a phenolic compound found in olive leaves and fruits and extra-virgin olive oil, which has well-known strong antioxidant and radical-scavenging properties. Recently, it has received particular attention for its antiproliferative and apoptotic activities and its anti-inflammatory properties. During the past few years, more efforts have been focused on synthesizing HTyr-derived compounds with enhanced biological activities for their potential use in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 108 publications
(236 reference statements)
0
68
0
Order By: Relevance
“…The highest cytotoxic activity was found by the ethers with the longest alkyl chain [40]. Similarly, these lipophilic derivatives inhibit both monocyte and macrophage pro-tumorigenic inflammatory activities and platelet function in a more effective way than HT [41], which reflects the broad applicability and importance of these type of molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The highest cytotoxic activity was found by the ethers with the longest alkyl chain [40]. Similarly, these lipophilic derivatives inhibit both monocyte and macrophage pro-tumorigenic inflammatory activities and platelet function in a more effective way than HT [41], which reflects the broad applicability and importance of these type of molecules.…”
Section: Discussionmentioning
confidence: 99%
“…On a positive note, it was noted that HT is a ‘safe’ compound and can be administered at higher doses without signs of any genotoxic or mutagenic effects (38; 39). Recently, there has been an interest in synthesis of HT-derivatives with a focus on improving the overall efficacy (40). A novel ester of hydroxytyrosol and alpha-lipoic acid was reported to enhance potency in colorectal cancer cells (41) through the induction of cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Tocopherols are present in olive oil in the forms α, β, γ, and δ, with 90% being found in the most biologically active α form, vitamin E [5]. Experimental evidence has demonstrated that the phenolic compounds present in EVOO possess numerous biological properties and are, at least partly, responsible for the beneficial effects arising from the consumption of EVOO [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%